Validation of the person-centered maternity care scale in India - Patience A. Afulani; Nadia Diamond-Smith; Beth Phillips; Shreya Singhal; May Sudhinaraset (BMC, 2018)
Abstract Background Person-centered care during childbirth is recognized as a critical component of quality of maternity care. But there are few validated tools to measure person-centered maternity care (PCMC). This paper aims to fill this measurement gap. We present the results of the psychometric analysis of the PCMC tool that was previously validated in Kenya using data from India. We aim to assess the validity and reliability of the PCMC scale in India, and to compare the results to those found in the Kenya validation. Methods We use data from a cross-sectional survey conducted from August to October 2017 with recently delivered women at 40 government facilities in Uttar Pradesh, India (N = 2018). The PCMC measure used is a previously validated scale with subscales for dignity and respect, communication and autonomy, and supportive care. We performed psychometric analyses, including iterative exploratory and confirmatory factor analysis, to assess construct and criterion validity and reliability. Results The results provide support for a 27-item PCMC scale in India with a possible score range from 0 to 81, compared to the 30-item PCMC scale in Kenya with a 0 to 90 possible score range. The overall PCMC scale has good reliability (Cronbach alpha = 0.85). Similar to Kenya, we are able to group the items in to three conceptual domains representing subscales for "Dignity and Respect," "Communication and Autonomy," and "Supportive Care." The sub-scales also have relatively good reliability (Cronbach alphas range from 0.67 to 0.73). In addition, increasing scores on the scale is associated with future intentions to deliver in the same facility, suggesting good criterion validity. Conclusions This research extends the PCMC literature by presenting results of validating the PCMC scale in a new context. The psychometric analysis using data from Uttar Pradesh, India corroborates the Kenya analysis showing the scale had good content, construct, and criterion validity, as well as high reliability. The overlap in items suggests that this scale can be used across different contexts to compare women's experiences of care, and to inform and evaluate quality improvement efforts to promote comprehensive PCMC.